2021
DOI: 10.3390/s21041235
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Horizon Air Pollution Forecasting with Deep Neural Networks

Abstract: Air pollution is a global problem, especially in urban areas where the population density is very high due to the diverse pollutant sources such as vehicles, industrial plants, buildings, and waste. North Macedonia, as a developing country, has a serious problem with air pollution. The problem is highly present in its capital city, Skopje, where air pollution places it consistently within the top 10 cities in the world during the winter months. In this work, we propose using Recurrent Neural Network (RNN) mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The forecast horizons are selected as 1, 6, 12, and 24 h ahead. This horizon configuration is based on the daily periodicity of the time series and is commonly adopted by recent works (Arsov et al, 2021;He et al, 2022). In adopted for training, with the batch size equal to 128 and a max epoch of 300.…”
Section: Dataset and Evaluation Settingmentioning
confidence: 99%
“…The forecast horizons are selected as 1, 6, 12, and 24 h ahead. This horizon configuration is based on the daily periodicity of the time series and is commonly adopted by recent works (Arsov et al, 2021;He et al, 2022). In adopted for training, with the batch size equal to 128 and a max epoch of 300.…”
Section: Dataset and Evaluation Settingmentioning
confidence: 99%
“…It was found that exogenous variables like weather parameters have shown considerable improvement in performance. LSTMs have also been used in traffic forecasting (Awan et al, 2020) and pollution classification (Arsov et al, 2021). Our research compares different machine learning models ranging from linear regression to multiple kernel based SVR techniques with both traditional mathematical models like ARIMA and the popular LSTM based deep learning models.…”
Section: Related Workmentioning
confidence: 99%
“…In the experiments, the authors predicted PM 2.5 for the next 1-8 h. The results showed the superiority of the proposed approach against SVR, GBT, and a standard LSTM model. Another RNN based model was proposed in [24] to forecast the concentration level of PM 10 at different future time steps (6, 12, and 24 h). On the other hand, Guo et al [25] proposed a feature engineering pipeline as well as a deep ensemble network algorithm which combines RNN, LSTM, and GRU networks to predict the PM 2.5 concentration of the next hour.…”
Section: Introductionmentioning
confidence: 99%